Integrating sustainability learning outcomes into a university curriculum: A case study of institutional dynamics. Issue 4 (8th May 2018) - Hill, Laura M.; Wang, Deane
Abstract : Purpose: Higher education institutions increasingly have gained momentum in integrating sustainability into university curricula. The purpose of this paper is to elucidate the approval, implementation and management process of the new university-wide, general education requirement in sustainability at the University of Vermont (UVM). The intent is to provide a case study to inform other institutions seeking to create similar university-wide sustainability requirements. Design/methodology/approach: The authors applied a process framework focused on institutional dynamics and values to analyze UVM's success in instituting a sustainability requirement across the curriculum. These two frameworks can provide a more general application of this case study to other institutional contexts. Findings: The case study suggests that in the context of a diverse disciplinary and administrative environment at a university, the strategic unfolding, approval and implementation of UVM's university-wide, general education sustainability requirement can provide a general model for other universities seeking to embed sustainability across the curriculum. Originality/value: It is uncommon for research universities with multiple professional schools to offer a university-wide requirement in sustainability. This case study analyzes the creation of a sustainability requirement at UVM by using a process framework to organize the complex, multi-stakeholder activities and events that eventually resulted in a successful curricular change. Thus, it is potentially instructive for institutions seeking to integrate a learning outcomes-based sustainability requirement into a university curriculum because it is generalizable to other institutions and pushes forward our understanding of institutional change.